The sufficiency of protection in light of the increasing number of cybercrime and cyber harassment cases - Witz, Daniel Joseph (University of the Witwatersrand, Johannesburg, 2022)
This research examines how the South African Police Services, the National Prosecuting Authority, current and new legislation and Criminal Law address harassment in light of the increased threat and technological advancements of cyberbullying and cyber harassment. This research assignment will critically reflect on whether the Protection from Harassment Act, supported by recent additions to South African legislation, affords an applicant sufficient protection considering the increasing number of cybercrime and cyber harassment cases, and whether or not the reliance on the South African Police Services and South African Courts negates any protection that the legislation affords. In conclusion, this research report will make certain recommendations regarding how the complex issues of harassment can be addressed to focus on the protection of South Africa's Constitutional Value
A research report submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2022
Keywords: Cyber harassment; Virtual reality; Cybercrime; South African Police Services; Criminal Law; Harassment Act; UCTD; SDG-9: Industry, innovation and infrastructure